FORMATION OF SOCIAL AND ETHICAL MARKETING IN THE ORGANIZATIONS ACTIVITIES - Безугла, Людмила; Куваєва, Тетяна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article examines the essence and features of the formation of socio-ethical marketing of organizations. It is established that modern business attaches great importance to its social responsibility in front of society and each of its members. Such responsibility may be most effectively implemented within socio-ethical marketing, as modern problems of optimizing the relationship between business and society can be solved within socio-ethical marketing. The essence and origin of the term «ethics» is studied and it is established that in the modern world ethics is connected with various spheres of human society, determines the morality and morality of its members, and regulates their behavior. It is proposed to develop a system model of socio-ethical marketing of organizations, which makes it possible to identify the essential elements of socio-ethical marketing and establish their dominant structural links. In order to survive during the competition, organizations need to be able to restructure and improve their products, their professional strategy and tactics, in general, all their activities, given the demands of time. Analysis of the scientific achievements of leading scientists in the field of socio-ethical marketing shows that ethical behavior is studied in terms of key principles of social responsibility. The organization’s behaviour should be based on a set of values such as honesty, integrity to people, animals, the environment. Changes in the country’s economy reveal a number of new pressing issues that are theoretical and methodological in nature and have scientific and practical significance for sustainable and dynamic development of organizations. Therefore, building a system of social responsibility and effective implementation of social investments from the point of view of society and the organization itself is an extremely important task for domestic business.